2005
DOI: 10.1093/annonc/mdi178
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of antisense oligonucleotide GTI-2040 given by continuous intravenous infusion in patients with advanced solid tumors

Abstract: The recommended dose of GTI-2040 given on this infusion schedule is 185 mg/m(2)/day. GTI-2040 appears to have a manageable toxicity profile and is generally well tolerated as a single agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…The starting dose of GTI-2040 was selected to be approximately 80% of the total dose of GTI-2040 administered safely during single agent solid tumor phase I studies (19). GTI-2040 infusion was followed by initiation of HiDAC to induce down-regulation of RNR before AraC exposure.…”
Section: Methodsmentioning
confidence: 99%
“…The starting dose of GTI-2040 was selected to be approximately 80% of the total dose of GTI-2040 administered safely during single agent solid tumor phase I studies (19). GTI-2040 infusion was followed by initiation of HiDAC to induce down-regulation of RNR before AraC exposure.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of using RRM2 mRNA inhibition as an anticancer strategy in humans is being tested by workers at Lorus Therapeutics (9). The results of a phase I trial of GTI-2040 given in patients with advanced solid tumors showed a manageable toxicity profile, and that it was generally well tolerated (10), leading to a phase I/II trial, in which GTI-2040 is given in combination with capecitabine to patients with metastatic renal cell carcinoma (11).…”
mentioning
confidence: 99%
“…47,48,50 Once in the cells, their effects are transient and diluted at each cell division, 51 so repeated dosing is required to achieve long-term therapeutic effects. Unmodified siRNA molecules also have potential toxicities, 52,53 via three main mechanisms, ie, saturation of RNAi machinery and competition within the miRNA pathway, stimulation of the immune response, and off-target effects.…”
Section: Difficulties In Therapeutic Applicationmentioning
confidence: 99%